Decay of accelerated protons and high energy astrophysics - Fregolente, D. [UNESP]; Matsas, G. E.A. [UNESP]; Vanzella, D. A.T. (World Scientific Publishing, 2006)
The possible relevance of the decay of accelerated protons in the context of high energy astrophysics is discussed.